ABNORMAL BLOOD LIPIDS LEVELS (DYSLIPIDEMIA) TREATMENT WITH ACUPUNCTURE METHOD - Rinjani, Anissa Maulina; Septriana, Maya; Herawati, Lilik (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: Dyslipidemia is an abnormal lipid metabolism characterized by an increase in total cholesterol, LDL (Low-Density Lipoprotein), triglycerides (TG), and a decrease in HDL (High-Density Lipoprotein). Increased levels of total cholesterol, TG, LDL, and decreased HDL levels can increase the risk of cardiovascular disease. According to TCM, dyslipidemia is categorized into